Data cleaning using OpenRefine - Magle, C. Tobin, speaker (Colorado State University. Libraries, 2018)
The process of generating data can be messy, especially when data are hand collected by multiple people. This month's Data and Donuts will discuss how to wrangle messy tabular data using OpenRefine (https://openrefine.org/), a free, open source tool for working with messy data. We will discuss the concepts of faceting, clustering, and splitting data. We will also show you how to export scripts to help you automate the cleaning process.
Data and donuts
Multiple sessions held on: 11/9/16, 3/28/17, 2/13/18.
Accessibility features: Unedited transcript.
To request an edited transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: data management; data education; Data editing; Data curation